Prognostic value of elevated cardiac and inflammatory biomarkers in patients with severe COVID-19: a single-center, retrospective study - Neeraj Kumar; Sarfaraz Ahmad; Mala Mahto; Abhyuday Kumar; Prabhat K. Singh (Emergency and Critical Care Medicine)
Abstract. Background. The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 in India has been declared a public health emergency. Many patients with COVID-19 experience cardiac injury. Patients with COVID-19 admitted to the intensive care unit (ICU) with acute myocardial injury showed increased high-sensitivity troponin levels. Abnormal troponin levels may indicate myocardial injury and are commonly associated with COVID-19. Methods. We conducted a retrospective observational study of 44 patients with severe COVID-19 in ICU during the second wave. The primary end point of our retrospective study was 28-day mortality, and the time of ICU admission was designated as day 0. We extracted and analyzed cardiac biomarkers, such as creatine kinase (CK), creatine kinase-MB (CK-MB), B-type natriuretic peptide (BNP), and high-sensitivity cardiac troponin I (hs-cTnI), and various inflammatory markers such as C-reactive protein (CRP) level, interleukin 6 (IL-6), d-dimer, ferritin, lactate dehydrogenase, IL-6, and procalcitonin in patients with severe COVID-19 at ICU admission and 72 hours after ICU admission from our electronic medical record system. Results. The best cutoff of BNP were 326.8 and 398.5 pg/mL, CK were 195.95 and 180.12 U/L, CK-MB were 112.10 and 108.5 U/L, and hs-cTnI were 0.035 and 0.025 ng/mL, at ICU admission and 72 hours after ICU admission for predicting 28-day mortality among nonsurvivors. Conclusion. In patients with severe COVID-19, CK and hs-cTnI may be considered effective and valuable predictive cardiac biomarkers among nonsurvivors and predict poor prognosis.